SIMULATION AND OPTIMIZATION DESIGN OF AIRFOIL HONEYCOMBS STRUCTURE - ZHANG MingMing; WU HongWei; WANG Shuai; MA BinJie (Jixie qiangdu)
For honeycomb structure,a analysis method based on equivalent theory combine with sub-model technology was proposed. The equivalent method based on sandwich plate theory is deduced and equivalent model of full height honeycombs structure is obtained. The global equivalent model of full height honeycombs structure is analyzed by finite element simulation,and sub-model analysis technology is applied to extract the region of interest from global equivalent model of full height honeycombs structure for detail analysis,the comparison of simulation and experimentation indicated the analysis method have better accuracy. Appling the analysis method for full height airfoil honeycombs structure,through simulation results investigated the relation between geometry parameters of full height airfoil honeycombs structure and per unit mass of instability failure load through simulations,moreover the result shows that per unit mass buckling load increases along with thickness of wing skin‘s and airfoil honeycombs structure cell’s wall grow,reduces along with thickness of airfoil honeycombs structure cell’s grows,besides in a bound which changes on the small side. Appling multi-objective optimization for full height airfoil honeycombs structure,the results show that per unit mass buckling load stay in great bound when the three geometry parameters of honeycombs structure’cell stay in a specifically bound.